Cherenkov EAS arrays in the Tunka astrophysical center: From Tunka-133 to the TAIGA gamma and cosmic ray hybrid detector - Kuzmichev, L; Astapov, I; Bezyazeekov, P; Borodin, A; Bruckner, M; Budnev, N; Chiavassa, A; Gress, O; Gress, T; Grishin, O; Dyachok, A; Fedorov, O; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2020)
One of the most informative methods of cosmic ray studies is the detection of Cherenkov light from extensive air showers (EAS). The primary energy reconstruction is possible by using the Earth's atmosphere as a huge calorimeter. The EAS Cherenkov light array Tunka-133, with similar to 3 km(2) geometrical area, is taking data since 2009. Tunka-133 is located in the Tunka Astrophysical Center at similar to 50 km west of Lake Baikal. This array allows us to perform a detailed study of the energy spectrum and the mass composition in the energy range from 6. 10(15) eV to 1018 eV. Most of the ongoing efforts are focused on the construction of the first stage of the detector TAIGA (Tunka Advanced Instrument for cosmic ray physics and Gamma Astronomy). The latter is designed for the study of gamma rays and charged cosmic rays in the energy range of 10(13) eV-10(18) eV. The TAIGA prototype will consist of similar to 100 wide angle timing Cherenkov stations (TAIGA-HiSCORE) and three IACTs deployed over an area of similar to 1 km(2). The installation of the array is planned to be finished in 2019 while the data-taking can start already during the commissioning phase. The joint reconstruction of energy, direction, and core position of the imaging and non-imaging detectors will allow us to increase the distance between the IACTs up to 800 m, therefore providing a low-cost, highly sensitive detector. The relatively low cost together with the high sensitivity for energies >= 30-50 TeV make this pioneering technique very attractive for exploring galactic PeVatrons and cosmic rays. In addition to the Cherenkov light detectors we intend to deploy surface and underground muon detectors over an area of 1 km(2) with a total area of about 1000 m(2). The results of the first season of coincident operation of the first similar to 4 m diameter IACT with an aperture of similar to 10 degrees. with 30 stations of TAIGA-HiSCORE will be presented.